Pharmacological inhibition of the RhoA pathway by melatonin reduces viral replication and proinflammatory response against ZIKV and DENV-4 neuroinfections - Bravo-Silva, José De Jesus; Jimenez-Camacho, Ricardo; Benítez-Vega, Magda Lizbeth; Hernández-Castillo, Jonathan; Cordero-Rivera, Carlos Daniel; Farfan-Morales, Carlos Noe; Pérez-García, Marcos; Cruz, Raymundo; del Ángel, Rosa María (Frontiers in Immunology, 2025)
IntroductionZika virus (ZIKV) and dengue virus (DENV) are mosquito-borne flaviviruses associated with serious neurological complications, such as Guillain-Barré syndrome and congenital Zika syndrome (ZIKV), as well as encephalitis, meningitis, and stroke (DENV). Despite their growing public health impact in tropical regions, there are currently no specific treatments available. Both viruses modulate the RhoA GTPase pathway, which is involved in immune regulation and cytoskeletal dynamics. Melatonin, a hormone with antioxidant and immunomodulatory properties, has previously been shown to inhibit Japanese encephalitis virus (JEV) replication through RhoA pathway modulation.MethodsWe evaluated the antiviral potential of melatonin against ZIKV and DENV-4 in vitro using U87-MG cells and in vivo using two mouse models: immunodeficient AG129 and neonatal immunocompetent CD1 mice. Antiviral and immunomodulatory effects were assessed by quantitative RT-PCR and analysis of inflammatory markers, including interferon-stimulated genes (MX1, IFI44L, IFN-β) and cytokines (IL-1β, TNF-α). Microglial activation and polarization were also analyzed in brain tissues.ResultsMelatonin treatment significantly reduced ZIKV and DENV-4 replication and the associated inflammatory response in U87-MG cells. In AG129 mice, melatonin increased survival, attenuated clinical signs during DENV-4 infection, and reduced viral genome copies of both viruses. In neonatal CD1 mice, melatonin markedly decreased viral loads in the brain and suppressed inflammatory gene expression, microglial activation, and M1/M2 polarization imbalance.DiscussionOur findings demonstrate that melatonin exerts both antiviral and anti-inflammatory effects against ZIKV and DENV-4 infections in vitro and in vivo, likely through inhibition of the RhoA signaling pathway. These results suggest that melatonin is a promising therapeutic candidate for neuroinfections caused by flaviviruses.